2020
DOI: 10.26434/chemrxiv.12181404.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-Silico Identification of Potent Inhibitors of COVID-19 Main Protease (Mpro) and Angiotensin Converting Enzyme 2 (ACE2) from Natural Products: Quercetin, Hispidulin, and Cirsimaritin Exhibited Better Potential Inhibition than Hydroxy-Chloroquine Against COVID-19 Main Protease Active Site and ACE2

Abstract: COVID-19 is rapidly spreading and there are currently no specific clinical treatments available. The absence of an immediate available vaccine against SARS-CoV-2 made it hard for health professionals to tackle the problem. Thus, the need of ready to use prescription drugs or herbal remedies is urgent. SARS-CoV-2 main protease (Mpro) and Angiotensin Converting Enzyme2 (ACE2) protein structure are made available to facilitate finding solutions to the present problem. In this brief research, we compare the effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Evidence: The anti-inflammatory potential that can be expressed on different cell types, both in animal and human models, is based on modulatory, biphasic, and regulatory action on inflammation and immunity. Additionally, quercetin demonstrates an immunosuppressive effect on dendritic cell function, downregulating Th2-derived production of interleukin 4 (IL-4) [30,31]. Hydroquercetin and quercetin (found in onions and apples) have been demonstrated to function as zinc ionophores by chelating zinc and transporting it into the cell cytoplasm in an in vitro model.…”
Section: Quercetinmentioning
confidence: 99%
“…Evidence: The anti-inflammatory potential that can be expressed on different cell types, both in animal and human models, is based on modulatory, biphasic, and regulatory action on inflammation and immunity. Additionally, quercetin demonstrates an immunosuppressive effect on dendritic cell function, downregulating Th2-derived production of interleukin 4 (IL-4) [30,31]. Hydroquercetin and quercetin (found in onions and apples) have been demonstrated to function as zinc ionophores by chelating zinc and transporting it into the cell cytoplasm in an in vitro model.…”
Section: Quercetinmentioning
confidence: 99%
“…These reports highlight a potential of flavonoids in mitigating SARS-CoV-2 viral infection via modulation of ACE2. Notably, as is highlighted later in this review, flavonoids like naringenin, naringin, nobiletin, hesperidin, hesperetin, neo-hesperidin, pinocembrin, quercetin, myricetin, and kaempferol have shown potential ACE2 binding affinity toward the residues that contact S protein of SARS-CoV-2 (Chen and Du, 2020;Cheng et al, 2020;Güler et al, 2020;Ngwa et al, 2020;Omar et al, 2020;Yang et al, 2020a).…”
Section: Natural Products and Ace2mentioning
confidence: 93%
“…This study identified 11 plants for their antiviral, antibacterial and antifungal activity based on low binding energy compared to the reference molecule (Joshi et al 2020). Sekiou et al compared the efficacy of hydroxychloroquine, Quercetin, Hispidulin, Cirsimaritin, Sulfasalazine, Artemisin and Curcumin natural compounds against COVID-19 using AutoDock indicated that these compounds have better potential inhibition than hydroxychloroquine (Omar et al 2020).…”
Section: In-silico Approachmentioning
confidence: 99%